Evaluation of the relationship between Doppler predictors with human papillomavirus types, smear and cervical biopsy results - Turhan Çakır, Anıl; Arslan, Aydan (The European Research Journal, 2022)
Objectives: The study aims to investigate whether there is any difference between human papillomavirus (HPV) types, smear results, and colposcopic biopsy results in terms of iliac, uterine, and cervical artery pulsatility and resistive index values in high-risk HPV positive patients.Methods: Iliac, uterine, and cervical artery pulsatility and resistive index values were determined by pelvic Doppler ultrasonography in patients who applied for high-risk HPV positivity and underwent colposcopyguided cervical biopsy.Results: There was no difference between HPV types and Pap-smear results and the pulsatility and resistive indices of the iliac artery, uterine artery, and cervical artery. It was observed that the mean cervical artery pulsatility index of the patients whose colposcopic cervical biopsy result was cervical intraepithelial neoplasia (CIN) 1 was 1.61 ± 0.43 and the cervical artery pulsatility index of the patients with CIN 2-3 was 1.15 ± 0.28, and a statistically significant difference was found between them (p = 0.038). There was no difference between other Doppler indices and colposcopic cervical biopsy results.Conclusions: Doppler indices such as cervical artery pulsatility index may be helpful in the evaluation of cervical cancer precursor lesions.